Phenotype wide association study links bronchopulmonary dysplasia with eosinophilia in children - Kelchtermans, Jelte; March, Michael E.; Hakonarson, Hakon; McGrath-Morrow, Sharon A. (Scientific reports, 2024)
Bronchopulmonary dysplasia (BPD) is a common complication of preterm birth. Despite this, genetic drivers of BPD are poorly understood. The objective of this study is to better understand the impact of single nucleotide polymorphisms (SNPs) previously associated with BPD by examining associations with other phenotypes. We drew pediatric subjects from the biorepository at the Center for Applied Genomics to identify associations between these SNPs and 2,146 imputed phenotypes. Methylation data, external cohorts, and in silico validation methods were used to corroborate significant associations. We identified 60 SNPs that were previously associated with BPD. We found a significant association between rs3771150 and rs3771171 and mean eosinophil percentage in a European cohort of 6,999 patients and replicated this in external cohorts. Both SNPs were also associated with asthma, COPD and FEV1/FVC ratio. These SNPs displayed associations with methylation probes and were functionally linked to ST2 (IL1RL1) levels in blood and lung tissue. Our findings support a genetic justification for the epidemiological link between BPD and asthma. Given the well-established link between ST2 and type 2 inflammation in asthma, these findings provide a rationale for future studies exploring the role of type 2 inflammation in the pathogenesis of BPD.